Propensity of Commercial Automotive Fuel for Boilover - Mohd Yusoff, Muhamad Syazwan (IRC, 2016)
Boilover is a ferocious discharge of fuel because of extended burning during a storage tank fire. It happens because of vaporisation of the water sub-layer that frequently resides at the base of a storage tank, bringing about the colossal fire enlargement, ejection of hot fuel from the tank, emergence of a fireball and a wide ground fire. Boilover is a greatly unsafe spontaneous occasion, which can prompt to serious injuries to emergency personnel. The boilover can happen a few hours after the fuel in a storage tank burst into flames.